Development of Interactive Media-Based Teaching Materials to Improve Conceptual Understanding of Measurement for Students at Makassar Maritime Polytechnic - Gradina Nur Fauziah; Agustina Setyaningsih; Annisa Rahmah; Napsawati Napsawati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research aims to develop and evaluate interactive media-based teaching materials to enhance conceptual understanding of measurement among students at Makassar Maritime Polytechnic. Conventional teaching methods, relying on textbooks and lectures, have proven ineffective in fostering the visual and spatial intuition necessary for maritime applications. Employing a modified 4D development model (Define, Design, Develop), the research created teaching materials using Flipbook PDF Professional, integrating text, images, videos, animations, and interactive quizzes in HTML5 format. Validation by experts yielded high scores: material validity at 91.11% and media validity at 95.45%, both categorized as "very valid." Practicality tests confirmed the materials were user-friendly and engaging. Effectiveness was demonstrated through a significant improvement in the experimental class, which achieved an average N-Gain of 0.672 (67.20%), classified as medium to high, compared to 0.192 (19.20%) in the control class. Statistical analysis revealed that 21.87% of experimental students reached "very high" understanding, with none in low categories. The findings conclusively show that the developed interactive teaching materials are valid, practical, and significantly more effective than conventional methods in improving conceptual understanding of measurement for maritime education.